HUBUNGAN RIWAYAT KEHAMILAN REMAJA (12-18 TAHUN) DAN JARAK KELAHIRAN DENGAN KEJADIAN STUNTING PADA BALITA DI PUSKESMAS PEKAUMAN BANJARMASIN - Pradini, Santia Andira; Ariani, Malisa; Fetriyah, Umi Hanik; Latifah, Hj (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2024)
Background: Teenage pregnancy can be a cause of stunting in children. This is because teenagers usually do not receive sufficient education regarding pregnancy and baby nutritional care. Stunting is a condition of failure to thrive in children under five years of age (toddlers) due to chronic malnutrition. Apart from the mother's history of teenage pregnancy, the birth spacing of toddlers is also a cause of stunting in toddlers. Objective: This study aims to analyze the relationship between history of teenage pregnancy and birth interval with the incidence of stunting in toddlers at the Pekauman Community Health Center, Banjarmasin. Method: Quantitative research with a descriptive correlation type with a cohort retrospective approach. The research was carried out in May-June 2023. The sample was 103 people using accidental sampling technique who met the inclusion criteria. Data were collected using anthropometric examination observation sheets and short interviews. Analyzed univariately and bivariately using the chi square test. Results: The number of mothers with completed elementary school/equivalent education was (76.7%), the number of mothers who did not work was (93.2%), the gender of the toddlers was female (55.3%), the number of toddlers aged 24-36 months was (78 .6%), 64 (62.1%) children under five experienced stunting, 84 (81.6%) teenage pregnancies and 55 (53.4%) normal birth spacing (≥2 years). The results of the analysis showed that there was a relationship between teenage pregnancy (p=0.000 < 0.05) with an OR value of 0.238 and birth spacing (p=0.000 < 0.05) with an OR value of 5.2 and the incidence of stunting among toddlers at the Pekauman Community Health Center, Banjarmasin. Conclusion: There is a relationship between a history of teenage pregnancy and birth spacing with the incidence of stunting among toddlers at the Pekauman Community Health Center, Banjarmasin. Therefore, it is important to educate teenagers and mothers about safe pregnancies aged >20 years, maintaining birth spacing >2 years and monitoring children's growth and development every month.